Cocaine effects on generation of reactive oxygen species and DNA damage: formation of 8-hydroxydeoxyguanosine in active abusers - Bacchi, Simona; Palumbo, Paola; Di Carlo, Massimo; Coppolino, Maria Francesca (International Journal of Pharmacology and Toxicology, 2016)
Cocaine abuse continues to be a major public health problem in the world. An upper numbers of individuals are initiating cocaine use with a stable rate of growth each year with an increasing number of people with cocaine related problems. Following cocaine oxidative pathways a ROS formation are generated. Oxidative stress has been demonstrated to play an important role in cocaine addiction and toxicity due to its oxidized metabolites produced by cytochrome P450 during cocaine biotransformation. The ROS induced genotoxicities include DNA damage, gene mutation, chromosome aberrations and micronuclei formation. 8-Hydroxy-2’-deoxyguanosine (8-OHdG) an oxidative modified DNA product, is the most representative product that may reflect oxidative damage induced by ROS. The present study was designed to investigate whether a systemic cocaine administration and its metabolism increase 8-OHdG production. Our findings clearly showed that cocaine promoted the ROS formation with significant increased of urinary 8-OHdG and MDA with a decreased of total scavenging capacity (TSC).